PENGARUH RASIO KEUANGAN TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yeni Alfiana; Dedeh Kurniasih (KOLEGIAL, 2013)
This study is performed to examine the effect of financial ratio consisting of current ratio, cash ratio, quick ratio, and net working capital toward Dividend Payout Ratio in manufacturing companies that is listed in Indonesian Stock Exchange over period 2009-2011. In sample, the study using purposive sampling method. Based on the criteria established by the research, the manufacturing companies listed on the Indonesian Stock Exchange was selected as the study observatios is 14 manufacturing companies. Data collection methods used in this study is secondary data data analysis techniques used is the multiple linear regression analysis. The research concludes that quick ratio give significantly effect on dividend payout ratio. And the other variables which is current ratio, cash ratio and net working capital are not significant to dividend payout ratio. Stimulatingly the Current Ratio, Cash Ratio, Quick Ratio and Net Working Capital have significant influence to Dividend Payout Ratio, it proved by sig-F value lower than 5% significances.